Work Islamic Ethics, Organizational Culture, Work Motivation on Citizenship Organization Behavior and Employees Performance at Bank Aceh Sharia - Yuliusdharma, Yuliusdharma; Likdanawati, Likdanawati; Khalsiah, Khalsiah; Wafi, Abdul (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Influence of Islamic work ethics, motivation on Organizational Citizenship behaviour and employee performance at Bank Aceh Syariah.Â  This study focused on all Islamic banking branch offices in Aceh Province, which amounted to Banda locations. By using primary data through interviews and questionnaires. Using the stratified proposition technique, namely the random sampling method and the structural inquiry model (SEM), and intervening variables. The study results show that commitment and loyalty significantly affect work culture values in Islamic Bank employees. The main fundamental principle is the Islamic work ethics created in Siddiq, Amanah, Tabligh, and Fatanah is the main basic principle. The work ethic becomes a mirror for employee performance. It shows a positive and significant influence on organizational culture and performance that can incentivize improving the climate positive corporate culture. Good. Furthermore, these factors will be analyzed and studied by examining the trends and leading features of the community's expertise. The researcher will conduct a Focus Group Discussion (FGD) to examine the findings. The achievement targets of this research are the publication of indexed international journals with the status of Submitted and International Proceedings Scopus Publish and Copyright with granted status. In the end, this research will produce a social policy that can use in Islamic banking services. The OCB factor has a very positive influence on trust in Islamic banks, which will make BPD Bank as mainstream Sharia the only one belonging to the people of Aceh and become the sole property of the Acehnese people.